It's a family affair: a case for consistency in family foundation giving and family firm community CSR activity - Cruz, Cristina (Journal of business ethics, 2024)
Although most business-owning families (BOFs) that operate large family firms practice community social engagement both in private via family foundations and in the business domain via community corporate social responsibility (CSR) programs, the relationship between their activities in the two domains remains unclear. Prior literature speculates that BOFs will deprioritize firms' community CSR when they have family foundations as more efficient vehicles to achieve socioemotional wealth (SEW), which would imply that such BOFs are less ethical in operating their firms. We contrast these speculations by enriching the socioemotional wealth (SEW) approach with instrumental stakeholder theory and cue consistency arguments and theorize that BOFs seek to ensure consistency between their activities in the two domains. Using data from 2008 to 2018 on the 95 largest US public family firms whose BOFs also operate private foundations, we show a positive relationship between family foundation giving and firm community CSR activity. Furthermore, we provide evidence for the boundary conditions of this relationship, showing that it is weaker for firms that do not share the family’s name and stronger for those firms with family leaders who also lead their families' foundations.